Collaborative Co-Teaching of a Secondary Science Methods Course: A Self-Study of Three Science Teacher Educators - Burgin, Stephen; Walker, Kate Ireton; Ward, Peggy (Innovations in Science Teacher Education, 2025)
In this manuscript, we present findings from a self-study of three science teacher educators, the authors of this manuscript, who collaborated in the planning and teaching of a secondary science methods course. The three of us, all from unique backgrounds and experiences, met regularly, recorded those meetings, and reflected on both the meetings themselves and the co-teaching experience. We also revisited the course over three years later to undergo another round of self-reflection and co-analysis. Results of this self-study document the refinement of the curriculum based on disciplinary expertise, an increased emphasis on the overlap between content and practice, professional community building within science teacher education, and individual growth as educators. In addition to the perceived successes of the collaboration, challenges and recommendations for other science teacher educators who want to co-teach methods courses are discussed. We especially want to encourage the underutilized partnership of methods instructors and field supervisors in co-teaching models.